Penerapan Teknologi Pengolahan Sampah Organik Dengan Metode Komposter Untuk Mewujudkan Lingkungan Zero Waste - Azteria, Veza; Veronika, Erna; Irfandi, Ahmad; Cucu Cahyanti; Mulyati Natul, Karolina; Aljunita, Intan; Keisha, Talitha; Yuliazahra, Aisyah (Universitas Medan Area, 2025)
Clean and healthy living behavior is one of the efforts made to improve the level of environmental health in the community. An implementation strategy must be implemented to educate the community on the importance of managing the environment correctly and adequately. Organic waste processing with a composter is not a new technology, but it is considered easy and inexpensive to implement in every household, especially for food waste. This community service increases community knowledge and skills in processing organic waste using a simple composter. To enable the community to utilize appropriate technology for waste processing, this community service was conducted in the RT 03 RW 01 area of Teluk Pucung Village, North Bekasi District, from October 2024 to December 2024. This activity was conducted using the counseling method, a direct practice by residents assisted by Mawar II Posyandu cadres. This community service performance was conducted for 2 days with 40 RT 03 RW 01 participants. Based on the results of the pre-test and post-test conducted on Teluk Pucung residents, it was found that there was an influence of knowledge and skills of residents, p-value of 0.025 before and after education. There needs to be intensive assistance to cadres and residents in managing organic waste so that this program can run sustainably.